Multiuser interaction with hybrid VR and AR for cultural heritage objects - Li, Yue; Ch'ng, Eugene; Cai, Shengdan; See, Simon (2018)
This research investigates the factors and ways in which users initiate conversations and engage in interactions in a hybrid virtual environment using a combination of Virtual Reality (VR) and Augmented Reality (AR) devices. The research was done in the ‘spirit of the ancient Silk Road’ where trade brought in exchange of ideas, cultural influence and cross-border communications. The notion of a 21st century Silk Road is necessarily digital, over the Internet and based around 3D cultural heritage objects. Digi-Capital’s Report forecasts the revenue of AR and VR to be US$150b by 2020. We projected that VR and AR will become pervasive, much like the Social Web and the universal ubiquity of mobile devices such as smartphones and wearables. Here, we conducted a user study exploring users’ acceptance of the use of hybrid VR and AR for cultural heritage, and investigated the social nature of multiple co-located user interaction. We adapted the UTAUT questionnaire in our experiment and found that social influence has positive effects on performance expectancy and effort expectancy, which generate positive effects on user behavioural intention. This study pioneers the future design and use of hybrid VR and AR technology in cultural heritage specifically, and in other application areas generally by highlighting the significant role that social influence plays in enhancing users’ behavioural intention facilitated by different immersive devices.